(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2023)
As an aspiration, positive peace is envisaged as a goal for society that requires an inter-relationship between non-violence, social justice and ecological sustainability, as proposed by Harris (2004). In this article, I am exploring a concept that is often taken for granted in analyses of positive peace, but which is often not discussed explicitly, although it is vital for establishing and ensuring positive peace. This is the concept of human relationships.